Tahlil Istikhdam Kitab al Lughah al Arabiyah fi al Manhaj 2013 (Dirasah al Halah fi Madrasah al Aliyah al Islamiyah al Hukumiyah Bangkalan) - M. Rofi’i; Siti Arinal Haq (Aqlamuna: Journal of Educational Studies, 2023)
Changes or updates to the curriculum are necessary because in fact the times are constantly developing and experiencing changes. Indirectly, the personality of students also experiences changes so that education must also make adaptations so that it can prepare the next generation that is able to compete in the future. Likewise in learning Arabic at Madrasah Aliyah Negeri (MAN) Bangkalan continues to innovate, especially in the Arabic teaching materials. However, the problems in the Arabic learning process faced by teachers and students continue even though Arabic books use publications from the Directorate General of Islamic Education, Ministry of Religion of the Republic of Indonesia in 2020 which refer to the curriculum 2013. The purpose of this research is to analyze and reveal problems in using books of Arabic Language in Curriculum 2013. This research method is a qualitative descriptive approach by means of observation, interviews with teachers and students and documentation in class XI MAN Bangkalan Academic Year 2022/2023. The results of this research are the use of Arabic books meets the good criteria, the teacher uses them according to the instructions in the book and the book is also equipped with four competencies as subject matter in Arabic language. However, students still feel the problems in terms of vocabulary that is difficult to understand, grammar (qawaid of arabic) which lacks explanation, meaningless Arabic texts, the difficulty of determining fi'il-fa'il sentences in reading (qira'ah) material, and the lack of explanation about listening (istima').